Improved SSF-cellulosic ethanol production by the cellobiose fermenting yeast Kluyveromyces marxianus G2-16-1 - Ancharida Akaracharanya (Science Faculty of Chiang Mai University, 2019)
Ethanol production from a cellulosic substrate by the simultaneous saccharification and fermentation (SSF) process was compared between the thermotolerant cellobiose fermenting yeast, Kluyveromyces marxianus G2-16-1, and the thermotolerant Saccharomyces cerevisiae G5-7-2 strain that had almost same efficiency to produce ethanol from glucose, as well as between them. The ethanol productivity of K. marxianus G2-16-1 from the lignocellulosic fiber of cassava waste pulp was 0.27 g L-1 h-1, some 1.17-fold higher than that for S. cerevisiae G5-7-2 (0.23 g L-1 h-1). Enhancement of the end-product inhibition effect of cellulase by the addition of 10% (w/v) carboxymethyl cellulose to increase the amount of digestible cellulose substrate and a two-fold increased level of cellulase into the SSF-cellulosic fermentation process increased the ethanol productivity of K. marxianus G2-16-1 1.78-fold to 0.48 g L-1 h-1, but decreased that for S. cerevisiae G5-7-2 to 0.21 g L-1 h-1. The co-culture of K. marxianus G2-16-1 with S. cerevisiae G5-7-2 could increase the ethanol productivity of S. cerevisiae G5-7-2 from 0.21 to 0.42 g L-1 h-1. Thus K. marxianus G2-16-1, which can hydrolyze cellobiose to glucose, is therefore able to accelerate the ethanol production rate from a cellulosic substrate in the SSF process.